Implementation of Problem-Based Learning Model in Islamic Education Learning to Explain Students' Critical Thinking Skills - Azwar Rahmat; Yesi Purwaningatamaja yesi; Lekat Fatma Juita lekat; Mahakus Sukri sukri (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
This study aims to examine the effect of implementing the Problem Based Learning (PBL) model on students’ critical thinking skills in Islamic Education (PAI) at SD Negeri 041 Bengkulu Utara. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The subjects consisted of two groups: an experimental class that applied the PBL model and a control class that used conventional teaching methods. Data were collected through a critical thinking skills test administered as pre-test and post-test, as well as observation sheets of student learning activities. The data were analyzed using descriptive and inferential statistics, including the independent sample t-test. The results revealed a significant difference between the critical thinking skills of students in the experimental and control groups, with a significance value of 0.000 < 0.05. The mean post-test score of the experimental group was higher than that of the control group. Furthermore, the N-Gain score of the experimental group was categorized as high (0.72), while the control group was categorized as moderate (0.41). These findings indicate that the implementation of the PBL model is effective in improving students’ critical thinking skills. In conclusion, the Problem Based Learning model can be recommended as an innovative and effective instructional strategy in Islamic Education, particularly in enhancing elementary school students’ critical thinking skills.